PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI SMAN 2 PAINAN - Silvia Fitriani (Jurnal Edukasi dan Penelitian Matematika, 2019)
Based on the results of daily test scores at SMAN 2 Painan, it was found that students' mathematical problem solving abilities were not optimal. This must be overcome because problem solving ability is one of the goals of mathematics learning. The 7E Learning Cycle learning model is one solution to this problem. The purpose of this study is to compare whether the mathematical problem solving abilities of students studying with the 7E Learning Cycle learning model are better than the mathematical problem solving abilities of students who learn with direct learning models in class XI of SMAN 2 Painan. Based on the test results, there is an increase in the ability of students studying with the 7E Learning Cycle model good than mathematical problem solving abilities of students who learn with direct learning models. It can be concluded that the 7E Learning Cycle model influences students' mathematical problem solving abilities. Keywords–The Abilityof Mathematical^Problem Solving, Direct Learning Model, Learning Cycle 7E Model.